(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
COVID-19 is a multisystem disease, and there is a high risk of thrombotic complications. The development of thrombotic complications in COVID-19 is due to an increase in the level of cytokines as a result of a pronounced inflammatory response. COVID-19 has a specific procoagulant effect, which is explained by its tropism for ACE2 in the vascular endothelium. The pathogenesis of thrombosis is associated with a decrease in endogenous fibrinolysis and an increase in platelet aggregation, as well as with the direct toxic effect of some drugs on the endothelium. Scientists warn that SARS-CoV-2 can damage blood vessels in children and lead to the development of hypertension, pulmonary hypertension, stroke and chronic kidney disease in the future.